Potencial turístico del cantón Chilla, provincia de El Oro, Ecuador. - Paez Valverde, Katherine Michelle (My University, 2019)
Chilla, belongs to one of the fourteen cantons of the province of El Oro, is located in a mountainous foothill of the Andes, has a single urban parish, which bears the same name. It is identified by having three areas which are: high, medium and low, which are important for the population because they facilitate the generation of economic income through agriculture and livestock. In addition, this canton contains lagoons, hills and beautiful views, which allows tourists to fall in love with their tourist tourists. Therefore, this research has as main objective to determine the tourism potential of the canton Chilla. The deductive - descriptive method was used, in addition to the methodology of hierarchy of tourist criteria and geographical spaces Mintur, 2017; the same that help to determine by means of the techniques used that the tourist potential of the Canton is in its natural resources; They allow diversity of flora and fauna, which allow the development of an ecotourism in the area.
Chilla, pertenece a uno de los catorce cantones de la provincia de El Oro, se ubica en una estribación montañosa la cordillera de los Andes, cuenta con una sola parroquia urbana, la cual lleva su mismo nombre. Se lo identifica por poseer tres zonas la cuales son: alta, media y baja, las cuales son de importancia para la población debido a que ellas facilitan a generar ingresos económicos por medio de la agricultura y ganadería. Además este cantón contiene lagunas, cerros y vistas hermosas, que permite que el turista se enamore de sus atractivos turísticos. Por ello la presente investigación tiene como objetivo principal determinar el potencial turístico del cantón chilla. Se empleó el método deductivo – descriptivo, además de la metodología de jerarquización de atractivos turísticos y espacios geográficos Mintur, 2017; las mismas que ayudaron a determinar mediante las técnicas utilizadas que el potencial turístico del Cantón está en sus recursos naturales; pues poseen diversidad de flora y fauna, que permiten el desarrollo de un ecoturismo en la zona.
Keywords: POTENCIAL TURÍSTICO; DESARROLLO TURÍSTICO; SISTEMA TURÍSTICO; JERARQUIZACIÓN